1998
DOI: 10.1017/s1355617798003361
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived picture priming in normal elderly persons and demented patients

Abstract: Normal elderly control participants showed short-term (10-min delay) and long-term (12 months delay) priming on the Gollin Figures Test. Nearly all patients with Alzheimer's disease or vascular dementia showed short-term priming, but the magnitude of their priming was less than that of controls. Significant long-term priming was not observed for the dementia groups. Differences between controls and dementia patients on the short-term priming test may depend upon structural–perceptual processes that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Typical repetition priming paradigms have an exposure either immediately followed by the testing phase or with a short delay. However, there were five studies that had a testing phase a year or more after the exposure phase (Beatty et al, 1998 ; Carlesimo et al, 1998 ; Mochizuki-Kawai et al, 2006 ; Ostergaard, 1994 ; Perri et al, 2007 ). A long delay is expected to yield different results when compared to same-day priming experiments, particularly given that individuals with aMCI or AD dementia often decline over time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical repetition priming paradigms have an exposure either immediately followed by the testing phase or with a short delay. However, there were five studies that had a testing phase a year or more after the exposure phase (Beatty et al, 1998 ; Carlesimo et al, 1998 ; Mochizuki-Kawai et al, 2006 ; Ostergaard, 1994 ; Perri et al, 2007 ). A long delay is expected to yield different results when compared to same-day priming experiments, particularly given that individuals with aMCI or AD dementia often decline over time.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these results were omitted in the current meta-analysis. This resulted in the exclusion of one study that only reported longitudinal priming effects (Beatty et al, 1998 ). For the other four studies, the short-term priming results were included in the current meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A secondary goal of this study was to examine the persistence of priming for unfamiliar objects over time in young and older adults. Studies using familiar stimuli have demonstrated priming following extended encoding-to-test delays (e.g., 52 weeks, Beatty, English, & Winn, 1998; 5 years, Kennedy, Rodrigue, & Raz, 2007), but all studies using unfamiliar stimuli tested priming immediately after the encoding phase. Because newly formed memory representations may be less stable over time or more susceptible to interference than representations of familiar words and objects, it is possible that priming for preexperimentally unfamiliar stimuli deteriorates and possibly disappears over time.…”
mentioning
confidence: 99%
“…Memory for familiar music can be somewhat maintained in AD (19)(20)(21)(22)(23). The ability to respond, recall, or produce music by singing, playing instruments, or composing is often preserved even in the severe stages of AD (24,25). When 7 Tesla functional brain magnetic resonance imaging (fMRI) and positron emission tomography (PET) compared AD regions of interest to the brain's response to music excerpts, regions such as the anterior cingulate cortex and ventral pre-supplementary motor area which encoded musical memory corresponded to areas, showed substantially minimal cortical atrophy and minimal disruption of glucose-metabolism (26).…”
Section: Music To Address Ad Neuropsychiatric Symptomsmentioning
confidence: 99%